Aspects of Early Israelite Religion in Judges 3:12-20 - Kalev, Zoran (Forum Theologicum Sardicense, 2025)
The goal of this article is to present the major theological points of Judges 3:12-30 (the deliverance cycle about Ehud and his mission as a judge), and, to arrive at a generalization about Israel‘s religious fervor in the setting of the Book of Judges.